PEARLS debriefing for social justice and equity: integrating health advocacy in simulation-based education - Niki Soilis; Elizabeth Anne Kinsella; Walter Eppich; Adam Cheng; Lindsay Beavers; Farhan Bhanji (Advances in Simulation)
Abstract Addressing health inequities in health professions education is essential for preparing healthcare workers to meet the demands of diverse communities. While simulation has become a widely recognized and effective method for providing safe and authentic clinical learning experiences, there has been limited attention towards the power of simulation in preparing health practitioners to work with groups who experience health disparities due to systems of inequality. Balancing technical proficiency with educational approaches that foster critical reflection and inform action oriented towards social accountability is essential. Transformational learning promotes the development of critical consciousness through critical reflection. Debriefing plays a crucial role in fostering learning in this direction by providing a structured opportunity to critically reflect on taken for granted assumptions, examine power and privilege embedded within systems and structures, and empower learners to take action toward changing those conditions. Building on the Promoting Excellence and Reflective Learning in Simulation (PEARLS) Healthcare Debriefing Tool, we propose a PEARLS Debriefing for Social Justice and Equity (DSJE) Tool that specifically directs attention to systems of inequality that contribute to health disparities for vulnerable groups across a range of simulation scenarios. This approach has two aims: (a) to transform debriefings into a critically reflective space by engaging learners in dialogue about social and structural determinants of health that may create or perpetuate inequities and (b) to foster critical reflection on what actions can be taken to improve the health and well-being of identified at risk and vulnerable groups. From this perspective, we can use the adapted PEARLS Tool to incorporate conversations about systems of inequality, equity, diversity, and inclusion (EDI) into our existing educational practices, and make concentrated efforts towards community-driven and socially conscious simulation-based education (SBE).